Transparency as a Way to Anticipate Tax Avoidance through Corporate Social Responsibility (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2019)
Not all CSR is based on firm’s ethical principle in running business. Occasionally, CSR is done to cover the opportunistic behavior of a firm, acting for its own interest. On the other hand, public firms are required to behave transparently as part of good corporate governance. Based on this framework, this research aims to know if transparency affects the relationship between CSR and tax avoidance. This study uses 162 samples of manufacturing firms listed in BEI, observed within the period of 2015-2017. Using multiple regression analysis in SPSS, this study proves that CSR and transparency affect the behavior of tax avoidance. The research also demonstrates that transparency is capable of mediating the relationship between CSR and tax avoidance